Synthesis, Processing and Application of Micro and Nanostructured Materials - Vasile, Bogdan Stefan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The book is focused on nanostructured materials, which have been well-studied in various fields from life to materials sciences. Nanostructured science has the potential to help make revolutionary discoveries based on modifying the properties of these materials compared with micro-structured materials. Nanostructured materials are the key to discovering new products based on new technologies. This book is focused on presenting new state-of-the-art methods for the synthesis and processing of nanostructured materials. These materials can be used in both in life and materials science with applications from biomedical devices, drug delivery systems, medical imaging with multiferoic materials, high-energy batteries, capacitors, superconductors, and aerospace components.